Fracture Properties of Graphene‐Coated Silicon for Photovoltaics. Issue 12 (20th September 2018) - Javvaji, Brahmanandam; Budarapu, Pattabhi Ramaiah; Paggi, Marco; Zhuang, Xiaoying; Rabczuk, Timon
Abstract: The possibility of replacing the conductive gridline deposited on solar cells by highly electrically conductive graphene is opening new perspectives for the future generation of photovoltaics. Besides enhanced electric performance, graphene can also have a role in the resistance of silicon against cracking. Here, the influence of depositing graphene on the silicon surface, on the fracture properties of silicon, is investigated. To pin‐point the influence of graphene, fracture properties estimated from molecular dynamics simulations of three different cases in uniaxial tension are compared. In the first case, the fracture properties of silicon alone are estimated in relation to different initial defect sizes. Second, the same simulations are repeated by depositing graphene on the silicon surface. Atomic interactions in the composite structure are modeled using the combined adaptive inter‐molecular reactive empirical bond order (AIREBO) and Tersoff potential functions. Improvement of about 780% in the Young's modulus of silicon is achieved after coating with graphene. Furthermore, to study the influence of realistic initial defects in graphene, a third set of simulations is considered by repeating the previous tests but with initial cracks through graphene and silicon. Predictions show that graphene can be highly beneficial in strengthening and repairing micro‐cracked silicon to decrease electrical power losses caused by cracks. Abstract : Here, molecular dynamics simulations explore the enhancement in fracture properties for graphene‐coated silicon compared to silicon alone. Detailed analysis of the bonding and non‐bonding interactions between carbon and silicon explore the possibility of first bond failure in the combined system. The graphene coating controls the crack propagation in silicon‐based photovoltaic cells.